Cleft of lip and palate: A review - Tarun Vyas; Prabhakar Gupta; Sachin Kumar; Rajat Gupta; Tanu Gupta; Harkanwal Preet Singh (Journal of Family Medicine and Primary Care, 2020)
Cleft of lip and palate are most common serial congenital anomalies to affect the orofacial region . It can occur isolated or together in various combination and/or along with other congenital deformities particularly congenital heart diseases. .Patient with oro-facial cleft deformity needs to be treated at right time and at right age to achieve functional and esthetic well being. Successful management of the child born with a cleft lip and palate requires coordinated care provided by a number of different specialties including oral/maxillofacial surgery, otolaryngology, genetics/dysmorphology, speech/language pathology, orthodontics, prosthodontics, and other. This article aims to the review the point primary care physicians in literature knowledge about cleft lip and palate. A review of literature have made to discuss introduction, epidemiology, clinical feature, etiology factor and management of cleft lip and palate.